2022
DOI: 10.1136/heartjnl-2021-320215
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental calcium and vitamin D and long-term mortality in aortic stenosis

Abstract: ObjectiveCalcium metabolism has long been implicated in aortic stenosis (AS). Studies assessing the long-term safety of oral calcium and/or vitamin D in AS are scarce yet imperative given the rising use among an elderly population prone to deficiency. We sought to identify the associations between supplemental calcium and vitamin D with mortality and progression of AS.MethodsIn this retrospective longitudinal study, patients aged ≥60 years with mild-moderate native AS were selected from the Cleveland Clinic Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The serum level of 1,25(OH) 2 D is tightly regulated by PTH, and it reflects both endogenous production and the effect of activated vitamin D 3 analogs in this study [ 16 , 33 ]. The relationship between serum calcium levels and the progression of AS has not been conclusively established [ 34 , 35 ]. However, calcium supplementation, with or without native vitamin D, has been associated with a higher incidence of future aortic valve replacement in elderly patients with mild to moderate AS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum level of 1,25(OH) 2 D is tightly regulated by PTH, and it reflects both endogenous production and the effect of activated vitamin D 3 analogs in this study [ 16 , 33 ]. The relationship between serum calcium levels and the progression of AS has not been conclusively established [ 34 , 35 ]. However, calcium supplementation, with or without native vitamin D, has been associated with a higher incidence of future aortic valve replacement in elderly patients with mild to moderate AS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between serum calcium levels and the progression of AS has not been conclusively established [ 34 , 35 ]. However, calcium supplementation, with or without native vitamin D, has been associated with a higher incidence of future aortic valve replacement in elderly patients with mild to moderate AS [ 35 ]. Among the patients in this study, one out of three (case 7) who were taking activated vitamin D 3 analog experienced AS progression along with an increase in serum calcium levels exceeding 10.5 mg/dL [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a small-scale study proposed a potential linear relationship between low levels of vitamin D and aortic valve peak flow velocity, as well as stenosis progression [114]. A retrospective study demonstrated significantly lower survival and a higher incidence of aortic valve replacement among patients receiving calcium supplements, with or without vitamin D, compared to those not receiving calcium [115]. Conversely, another study found phosphate, but not calcium or vitamin D, to be significantly related to aortic valve stenosis incidence [116].…”
Section: Aortic Stenosismentioning
confidence: 99%
“…Vitamin D deficiency tends to be common, although supplementation has not shown an improvement in quality of life, biochemical parameters, CV death, or hospitalization [1,38,41]. In some cases, calcium supplementation, alone or routinely combined with vitamin D, has been associated with decreased survival and an increased CV risk in older patients with mild-to-moderate aortic stenosis [48]. Therefore, the general recommendation would be to supplement only in cases of deficiency.…”
Section: Other Micronutrientsmentioning
confidence: 99%